The investigation in terminology. The relevancy of the oral corpus for certain professional languages - M. García Antuña (Ибероамериканские тетради)
This work is part of a multilingual terminographic project in the lexical field of leather goods. We present the guidelines we followed and the difficulties we met in setting up bases of the corpus extracted from oral sources. The scarcity of written documentary sources in certain sub-themes of the lexical field of leather goods considerably complicated carrying out the systematic work. Consequently, it was necessary to solve the methodological problems caused by the absence of a written corpus which would be representative for all thematic areas. This was settled by the development of an oral corpus.